José Antonio Primo de Rivera : the reality and myth of a Spanish fascist leader - Thomàs, Joan Maria (Studies in Latin American and Spanish history, 2019)
"There are few individuals in modern Spanish history that have been as thoroughly mythologized as José Antonio Primo de Rivera, a leading figure in the Spanish Civil War who was executed by the Republicans in 1936 and celebrated as a martyr following the victory of the Falangists. In this long-awaited translation, Joan Maria Thomàs provides a measured, exhaustively researched study of Primo de Rivera's personality, beliefs, and political activity. His biography shows us a man dedicated to the creation of a fascist political regime that he aspired to one day lead, while at the same carefully distinguishing his aims from those of the Falangists and the Franco Regime"--